“Where I’m From”: Utilizing Place-Based Pedagogy and Multimodal Literacy in a Graduate Children’s Literature Class - Stephanie M Bennett (Middle Grades Review, 2016)
In this study, I examined integrating place-based education pedagogy and multimodal literacies into a graduate level children’s literature class. The findings suggest including place-based education pedagogy allows middle level graduate students to connect to geographically-based children’s literature. The findings also propose that incorporating multimodal texts into classroom assignments expands graduate students perceptions of text. Implications for implementing the assignment into 4-8 grade classes is discussed.
Keywords: place-based pedagogy; multimodal texts; children' s literature